Barriers to Community Integration for Older People in Malaysia: A Qualitative Study from Occupational Therapist Perspectives - Yau Y. Hui; Nathan Vytialingam,Sangeeta K. Singh (Public Health, 2025)
IntroductionExisting research has addressed the importance of community integration (CI) and its benefits of dwelling in a community but has yet to address the methods and efficiency of improving these activities among older people. Thus, it is vital to understand how healthcare workers can integrate the benefits of CI among older people, especially with the use of occupational therapists (OTs). The latter are actively working to improve ageing individuals mobility within the community.ObjectiveThis study aims to identify Malaysian OTs’ perspectives on CI’s and its implication on older people.MethodOccupational therapist from different states of Malaysia participated in a semi-structured interview, through a virtual medium (Zoom Cloud Meetings). The interview guide encapsulated the theory of critical incident technique (CIT).ResultsThematic content analysis, over fourteen participants from 13 states of Malaysia, provided insights into CI’s barriers for older people in Malaysia. The findings revealed that multifaceted factors from an individual, organisational and socio-environmental perspective limit older people’s active CI engagement.ConclusionSouth-East Asia hierarchal and collectivist culture play a significant role in influencing all factors of CI. OTs must understand and incorporate appropriate cultural norms during CI practice development for the older population in Malaysia.